2022
DOI: 10.1111/psyp.14216
|View full text |Cite
|
Sign up to set email alerts
|

Error‐related brain activity: A time‐domain and time‐frequency investigation in pediatric obsessive–compulsive disorder

Abstract: Increased error-related negativity (ERN), a measure of error monitoring, has been suggested as a biomarker of obsessive-compulsive disorder (OCD). Additional insight into error monitoring is possible using time-frequency decomposition of electroencephalographic (EEG) data, as it allows disentangling the brain's parallel processing of information. Greater error-related theta is thought to reflect an error detection signal, while delta activity may reflect more elaborative post-detection processes (i.e., strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…This is an open-access software that performs statistical correction for multiple comparisons by identifying spatio-temporal event-related differences and tests their statistical significance using baseline values derived from Monte-Carlo simulated data [ 53 ]. Details of this statistical approach can be found in previous publications from our group [ 4 , 42 , 55 , 56 ] and other groups [ 57 61 ]. Briefly, cluster-based statistics rely on a data-driven distribution of the test statistic and the initial non-permuted test statistic is compared against the shuffled distribution and a cluster-level correction was applied [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is an open-access software that performs statistical correction for multiple comparisons by identifying spatio-temporal event-related differences and tests their statistical significance using baseline values derived from Monte-Carlo simulated data [ 53 ]. Details of this statistical approach can be found in previous publications from our group [ 4 , 42 , 55 , 56 ] and other groups [ 57 61 ]. Briefly, cluster-based statistics rely on a data-driven distribution of the test statistic and the initial non-permuted test statistic is compared against the shuffled distribution and a cluster-level correction was applied [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…A specific physiological measure of error monitoring is EEG error-related negativity (ERN), which arises as a negative electrocortical deflection in the ERP at frontocentral scalp sites within 100 ms following the commission of an error vs. a correct response (Gehring et al, 1995). The ERN has been mostly employed in the study of anxiety disorders (e.g., Meyer et al, 2018a), but there is some evidence that the ERN is blunted in adults and children with clinical depression (Ruchsow et al, 2004(Ruchsow et al, , 2006Schrijvers et al, 2008;Weinberg et al, 2015c;Dell'Acqua et al, 2023) and depression risk (Meyer et al, 2018b;Tabachnick et al, 2018). For instance, Meyer and colleagues reported that the offspring of women with recurrent MDD had a reduced ERN relative to a control group, even when accounting for maternal anxiety (Meyer et al, 2018b).…”
Section: Event-related Potentialsmentioning
confidence: 99%
“…Some models on the ERN suggest that this measure acts as an early warning signal following the commission of an error evaluating the need to raise cognitive control resources allocated to the task (Weinberg et al, 2016). As previously described, the literature on the ERN in depression and its risk is still conflicting, with studies evidencing reduced (Ruchsow et al, 2004(Ruchsow et al, , 2006Schrijvers et al, 2008;Weinberg et al, 2015a;Meyer et al, 2018b;Tabachnick et al, 2018;Dell'Acqua et al, 2023) or greater ERN (Chiu and Deldin, 2007;Holmes and Pizzagalli, 2010) in these groups.…”
Section: Event-related Potentialsmentioning
confidence: 99%
“…A systematic review focused on the currently proposed neurocognitive endophenotypes of pediatric OCD in 43 studies, finding that abnormal action monitoring is considered a robust endophenotypic feature of pediatric OCD, which has been confirmed by high amplitudes of ERN and abnormal activation in ACC; intolerance of uncertainty, possible impairment of planning ability and the hyperactivity of the frontoparietal regions in working memory tasks are potential endophenotypes, though the results of the available studies are inconsistent [ 92 ]. A recent study has provided insights into error-related brain activity in pediatric OCD by time-domain and time-frequency analysis, suggesting that pediatric OCD may be characterized by enhanced error monitoring (i.e., greater theta power) and post-error inhibition (i.e., greater beta power) [ 93 ]. However, the participants selected for the study were only pediatric OCD patients, which means the current result has not been validated in their unaffected relatives.…”
Section: Primary Secondary and Tertiary Prevention Of Pediatric Ocdmentioning
confidence: 99%